Phytoplankton Diversity as Ecological Indicator in Jimbaran Bay Waters - Perwira, Ima Yudha; Ulinuha, Devi (Journal of Environment)
A study was carried out to evaluate the ecological condition in Jimbaran Bay Waters by using Phytoplankton Diversity Index. The study was conducted at Balangan, Pemuda, Jimbaran, Kedonganan, Kelan and Segara Beach located in Jimbaran Bay. Shannon-Wiener diversity index was used to analyze the ecological condition, supported by analysis on water quality including dissolved oxygen (DO), biological oxygen demand 5 days (BOD5), water pH, and water salinity. There were 51 species of phytoplankton classified to 5 classes had been observed from this study: Bacillariophycae, Cyanophyceae, Zygnemophyceae, Dinophyceae, and Chlorophyceae. Balangan beach showed higher diversity index (H) and evenness index (E) (H = 1.19; E = 0.29) compared to the other site (Pemuda: H = 0.89, E = 0.25; Jimbaran: H = 0.89, E = 0.26; Kedonganan: H = 0.96, E = 0.28; Kelan: H = 0.85, E = 0.20; and Segara: H = 0.91, E = 0.33). However, overall ecological condition showed diversity index more than 1 (H = 1.44; E = 0.27). Measurement of water quality showed that the highest quality of water was shown by Balangan Beach (DO 5.2 mg/L, pH 7.2, salinity 29 ppt, and BOD5 0.9 mg/L), while the lowest was shown by Kelan Beach (DO 4.2 mg/L, pH 7.2, salinity 29 ppt, and BOD5 2.9 mg/L). Result of the study showed that ecological status of Jimbaran Bay Waters was having moderate diversity, sufficient productivity, and medium ecological pressure (pollution).